2013
DOI: 10.1021/jm301302s
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent, Selective Multidrug and Toxin Extrusion Transporter 1 (MATE1, SLC47A1) Inhibitors Through Prescription Drug Profiling and Computational Modeling

Abstract: The human multidrug and toxin extrusion (MATE) transporter 1 contributes to the tissue distribution and excretion of many drugs. Inhibition of MATE1 may result in potential drug-drug interactions (DDIs) and alterations in drug exposure and accumulation in various tissues. The primary goals of this project were to identify MATE1 inhibitors with clinical importance or in vitro utility and to elucidate the physicochemical properties that differ between MATE1 and OCT2 inhibitors. Using a fluorescence assay of ASP+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 53 publications
9
117
2
Order By: Relevance
“…We have described the use of seven data sets representing six transporters of interest (MATE1, MATE2K, OCT2, OCTN2, ASBT, and NTCP) due to their potential involvement in drug-drug interactions (Diao et al, 2009Zheng et al, 2009;Kido et al, 2011;Astorga et al, 2012;Ekins et al, 2012b;Greupink et al, 2012;Dong et al, 2013Dong et al, , 2014Sedykh et al, 2013;Wittwer et al, 2013;Xu et al, 2013). We focused on Bayesian models with ECFP6 and FCFP6 descriptors because these were previously used to develop models that were successfully validated using prospective testing.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have described the use of seven data sets representing six transporters of interest (MATE1, MATE2K, OCT2, OCTN2, ASBT, and NTCP) due to their potential involvement in drug-drug interactions (Diao et al, 2009Zheng et al, 2009;Kido et al, 2011;Astorga et al, 2012;Ekins et al, 2012b;Greupink et al, 2012;Dong et al, 2013Dong et al, , 2014Sedykh et al, 2013;Wittwer et al, 2013;Xu et al, 2013). We focused on Bayesian models with ECFP6 and FCFP6 descriptors because these were previously used to develop models that were successfully validated using prospective testing.…”
Section: Resultsmentioning
confidence: 99%
“…We previously published several transporter models and described Bayesian models generated using Discovery Studio (Biovia, San Diego, CA) for MATE1, MATE2K, OCTN2, ASBT, and NTCP (Diao et al, 2009Zheng et al, 2010;Astorga et al, 2012;Dong et al, 2013Dong et al, , 2014. We have now analyzed several larger published data sets from other groups for MATE1 (Wittwer et al, 2013) and OCT2 (Kido et al, 2011), which we have also used to generate Bayesian models with Discovery Studio to compare the different fingerprints. To illustrate the utility of transporter models built with open ECFP6 descriptors and the Bayesian algorithm, 5-fold cross-validation and leave-one-out validation were used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it has been suggested that different pharmacophore hypotheses in the CP model may correspond to different inhibitory mechanisms, which can explain the structural diversity of OCT2 inhibitors. Subsequently, Giacomini's team published their research on another important emerging renal transporter, MATE1, and found 84 inhibitors among 900 prescription drugs (Wittwer et al 2013). These authors developed an RF model with an average AUC value of 0·78.…”
Section: Membrane Transportersmentioning
confidence: 99%